Cross-Strait Relations: No Return to Crisis Mode - Char, James (2016)
The common belief that cross-strait relations is headed for instability following the DPP’s election victory is overstated. Although there could be more friction with Beijing, the Taiwan Strait is unlikely to witness a return to previous crisis levels.